Three New Non-reducing Polyketide Synthase Genes from the Lichen-Forming Fungus Usnea longissima - Wang, Yi; Wang, Juan; Cheong, Yong Hwa; Hur, Jae-Seoun (Mycobiology, 2014)
Usnea longissima has a long history of use as a traditional medicine. Several bioactive compounds, primarily belonging to the polyketide family, have been isolated from U. longissima. However, the genes for the biosynthesis of these compounds are yet to be identified. In the present study, three different types of non-reducing polyketide synthases (UlPKS2, UlPKS4, and UlPKS6) were identified from a cultured lichen-forming fungus of U. longissima. Phylogenetic analysis of product template domains showed that UlPKS2 and UlPKS4 belong to group IV, which includes the non-reducing polyketide synthases with an methyltransferase (MeT) domain that are involved in methylorcinol-based compound synthesis; UlPKS6 was found to belong to group I, which includes the non-reducing polyketide synthases that synthesize single aromatic ring polyketides, such as orsellinic acid. Reverse transcriptase-PCR analysis demonstrated that UlPKS2 and UlPKS4 were upregulated by sucrose; UlPKS6 was downregulated by asparagine, glycine, and alanine.